Essai d’utilisation du «Conversational Analysis Profile for People with Aphasia» (CAPPA) - Chetelat-Mabillard, Daphné; Buttet Sovilla, Jocelyne (My University, 2003)
The Conversational Analysis Profile for People with Aphasia is a good complement to the neuropsychological examination for aphasic patients. We have translated the CAPPA in order to propose it to some French speaking persons. The use of this tool has raised some questions that will be discussed in this paper. After a presentation of the CAPPA, a clinical example will illustrate how the answers of the patient and those of her conversational partner were analysed.